Ayni and Minka, two collective forms of Work pre-Chavin societies - Altamirano Enciso, Alfredo Jose (2011)
This article shows the origins of ayni and minka, autochthonous forms of communal work own of Andean region that begun since Late Archaic Period and Formative, between 3200 and 1800 b.C. in four ceremonial centers of central and north coast and north highland. It is done a comparative study between two groups: one is Las Haldas temple and Cardal site that had used shicras (vegetal fiber) and small stones, nonetheless the second formed by La Galgada and Pacopampa, in Ancash and Cajamarca departments, respectively, their architectures describe the use of great stones, terraces and strong structures like indicators minka, realized by several human groups in competence. Ayni of the central coast means reciprocity and work of societies without classes like fishermen and crayfish-men; by other hand minka is related to herders, farmers, stone-men-work and specialized groups like beginning of the social classes.